2017
DOI: 10.1093/europace/eux265
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk score for predicting atrial fibrillation recurrence after a first catheter ablation procedure – ATLAS score

Abstract: A simple risk score to estimate the rate of AF recurrence after ablation was developed and validated. An external assessment of its usefulness as a patient selection tool seems warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 28 publications
3
69
0
2
Order By: Relevance
“…6,7 This has led to a search for predictors of ablation success, such as type of AF, presence of structural heart disease, left atrial size, age, and sex. [8][9][10][11] In our group's experience, a large surge in vagal tone during catheter ablation correlates with a postprocedural increase in resting HR following the ablation procedure. We have also observed that our patients who have significant HR increases at the time of hospital discharge have better outcomes during follow-up.…”
Section: Disruption Of Vagal Reflexes During Pulmonary Vein Isolationmentioning
confidence: 81%
“…6,7 This has led to a search for predictors of ablation success, such as type of AF, presence of structural heart disease, left atrial size, age, and sex. [8][9][10][11] In our group's experience, a large surge in vagal tone during catheter ablation correlates with a postprocedural increase in resting HR following the ablation procedure. We have also observed that our patients who have significant HR increases at the time of hospital discharge have better outcomes during follow-up.…”
Section: Disruption Of Vagal Reflexes During Pulmonary Vein Isolationmentioning
confidence: 81%
“…Age > 60 years (1 point), type of AF-non-paroxysmal (2 points), indexed left atrial volume (1 point for each 10 mL/m 2 ) female sex (4 points) and current smoking (7 points) were detected as independent predictors for arrhythmia recurrences after CA and they were included in the ATLAS score. 28 3.9 | ABC death risk score Age, heart failure in the clinical history, N-terminal pro-B-type natriuretic peptide, troponin-T, and growth differentiation factor-15 levels were included in the ABC death risk score. 24…”
Section: Atlasmentioning
confidence: 99%
“…The ATLAS score has been developed in a cohort of 1934 AF patients undergoing first CA which were divided into a development and a validation cohort (50% each). 28 9 and was defined as any region with <0.5 mV 23 during electro-anatomical voltage mapping. Voltageguided substrate modification by targeting LVA in addition to circumferential pulmonary vein isolation (PVI) is more effective than conventional PVI ablation approaches concerning arrhythmia freedom after the ablation.…”
Section: Atlasmentioning
confidence: 99%
“…In clinical practice, elderly patients are prone to AF recurrence as a result of long‐term progressive atrial scarring. Evidence also shows that advanced age (>60 years for the ATLAS score, >50 years for the CAAP‐AF score) is a contributor to the risk of AF recurrence after catheter ablation, constraining the application of catheter ablation including CBA in the elderly population. The outcome of CBA in the elderly population had not been specifically investigated until 2016.…”
Section: Discussionmentioning
confidence: 99%